2015
DOI: 10.1097/aog.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Intramuscular Treatment Options for Early Postpartum Endometritis in Low-Resource Settings

Abstract: This review provides suggestions for oral, intramuscular, and combined antimicrobial regimens that may warrant additional study. Experimental trials should consider clinical effectiveness, safety and side effects profiles, and feasibility of community-based treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 63 publications
0
12
0
3
Order By: Relevance
“…9 Endometritis was excluded as it is considered an organ space infection separate from wound infection and is thought to be an ascending and polymicrobial infection not generally attributable to skin pathogens. [9][10][11] Subgroup analyses of studies including superficial versus deep wound infection and povidoneiodine solutions with versus without alcohol were conducted for the primary outcome of overall surgical site infection. Secondary outcomes included wound seroma, hematoma, skin separation, and skin reaction.…”
Section: Discussionmentioning
confidence: 99%
“…9 Endometritis was excluded as it is considered an organ space infection separate from wound infection and is thought to be an ascending and polymicrobial infection not generally attributable to skin pathogens. [9][10][11] Subgroup analyses of studies including superficial versus deep wound infection and povidoneiodine solutions with versus without alcohol were conducted for the primary outcome of overall surgical site infection. Secondary outcomes included wound seroma, hematoma, skin separation, and skin reaction.…”
Section: Discussionmentioning
confidence: 99%
“…After informed written consent, clinical diagnostic specimens, including urine, blood, and endometrial, were collected from these confirmed puerperal sepsis cases. All women with puerperal sepsis were prescribed recommended first-line antibiotics (amoxicillin-clavulanate or oral clindamycin with intramuscular gentamicin) based on a recent metaanalysis [4], unless otherwise indicated by the laboratory results.…”
Section: Methodsmentioning
confidence: 99%
“…Wenn sich innerhalb von 48 h die klinische Symptomatik nicht bessert, sollte zusätzlich das Anaerobierspektrum durch Metronidazol plus Gentamicin (3 × 1,5 mg/ kgKG i. v./Tag oder Einzeldosis: 5 mg/kgKG i. v./Tag abgedeckt werden [17].…”
Section: Antibiotika Der Wahl Sind Kombinationstherapien Mitunclassified
“…Durch die Endotoxinproduktion, insbesondere der Streptokokken der Gruppe A, kommt es zu einer ausgedehnten Gewebezerstörung; dies kann damit zu foudroyanten lebensbedrohlichen Verlaufsformen durch das Multiorganversagen führen. Ein rascher Therapiebeginn mit breiter Antibiose in Zusammenarbeit mit Intensivmedizinern ist daher therapieentscheidend [17]. Hierbei sollten die Therapieempfehlungen der Paul-Ehrlich-Gesellschaft berücksichtigt werden [17].…”
Section: Puerperalsepsisunclassified
See 1 more Smart Citation